Lead, mercury, and selenium alter physiological functions in wild caimans (Caiman crocodilus). (1st October 2021) - Lemaire, Jérémy; Bustamante, Paco; Mangione, Rosanna; Marquis, Olivier; Churlaud, Carine; Brault-Favrou, Maud; Parenteau, Charline; Brischoux, François
Abstract: Environmental contaminants affect ecosystems worldwide and have deleterious effects on biota. Non-essential mercury (Hg) and lead (Pb) concentrations are well documented in some taxa and are described to cause multiple detrimental effects on human and wildlife. Additionally, essential selenium (Se) is known to be toxic at high concentrations but, at lower concentrations, Se can protect organisms against Hg toxicity. Crocodilians are known to bioaccumulate contaminants. However, the effects of these contaminants on physiological processes remain poorly studied. In the present study, we quantified Hg, Pb and Se concentrations in spectacled caimans ( Caiman crocodilus ) and investigated the effects of these contaminants on several physiological processes linked to osmoregulatory, hepatic, endocrine and renal functions measured through blood parameters in 23 individuals. Mercury was related to disruption of osmoregulation (sodium levels), hepatic function (alkaline phosphatase levels) and endocrine processes (corticosterone levels). Lead was related to disruption of hepatic functions (glucose and alanine aminotransferase levels). Selenium was not related to any parameters, but the Se:Hg molar ratio was positively related to the Na + and corticosterone concentrations, suggesting a potential protective effect against Hg toxicity. Overall, our results suggest that Hg and Pb alter physiological mechanisms in wild caimans and highlight the need to thoroughly investigate the consequences of trace element contamination in crocodilians. Graphical abstract: Image 1 Highlights: Trace element concentrations affect physiological parameters in caimans. Mercury concentrations disrupt osmoregulation, hepatic and endocrine functions. Lead concentrations disrupt hepatic function. Selenium is related to protective effect against mercury toxicity.